Розробка компонентів платформи дистанційного навчання - Бурика, О. О. (ХНУРЕ, 2024)
During this work, a learning management system was developed. It is designed for distance learning. This system allows anyone to browse the catalog of available courses and get information available for free viewing. However, full access to the course is provided only after its purchase. The system provides the following roles for accessing the system: unregistered user, client, and administrator. Each of them has different levels of access. The system is well designed and contains only relevant information so that all users can easily find what they are interested in. The use of modern technologies automates the processes of providing information, ordering and reporting.
Keywords: дистанційне навчання; distance learning